53Mn-53Cr systematics of sphalerite in enstatite chondrites. (1st October 2021) - Hopp, Jens; Storck, Julian-Christopher; Ludwig, Thomas; Mostefaoui, Smail; Altherr, Rainer; Ott, Ulrich; Meyer, Hans-Peter; Trieloff, Mario
Highlights: Mn-Cr systematics of sphalerite in five E chondrites was established by SIMS. Mn-Cr system appears affected by weathering processes in MAC 88136. Other disturbances could relate to complex thermal histories. Substantial variation in initial 53 Mn/ 55 Mn still limits chronologic applications. Chronologic potential is recognizable but requires additional research. Abstract: We investigated the 53 Mn- 53 Cr isotopic composition of a suite of enstatite chondrites by in situ analyses of various mineral phases with the Cameca IMS 1280-HR ion probe at Heidelberg, Germany, and a Cameca NanoSIMS at Paris, France. Only in sphalerite we found anomalies in 53 Cr/ 52 Cr-ratios correlating with 55 Mn/ 52 Cr which are due to decay of short-lived 53 Mn (t1/2 = 3.7 Ma). A sphalerite in the EH-impact melt LAP 02225 showed the largest excess of 53 Cr, with 53 Cr/ 52 Cr-ratios ranging up to 2.2. The calculated initial 53 Mn/ 55 Mn-ratios are within the range of previous Mn-Cr studies. We observed a spatial variation within a large sphalerite in LAP 02225, translating in distinct initial 53 Mn/ 55 Mn values. In case of the EL3 chondrite MAC 88136 the initial 53 Mn/ 55 Mn derived for one sphalerite is at the lower end of previously reported values and may reflect a variable influence of alteration-induced exchange of common Cr. This is supported by the total reset of the 53 Cr/ 52 Cr-ratio in another sphalerite in contact with an alteration vein irrespective of high Mn/Cr-ratios. Our observed initial 53 Mn/ 55 Mn-ratios of Sahara 97158, Indarch and EET 96135 correspond to the I-Xe systematics and hence, show that sphalerites can preserve reasonable age information. For Indarch however, if compared with other initial 53 Mn/ 55 Mn values from literature, a considerable scatter is obvious. This clearly demonstrates that the Mn-Cr system in sphalerite can be disturbed by various, still poorly investigated, processes (e.g., by thermal events, weathering, diffusion-controlled remobilization). Future application of Mn-Cr dating to sphalerite in enstatite chondrites thus requires a better understanding of how such processes influence the Mn-Cr systematics and demands for tools to identify the undoubtly present sphalerites carrying a true chronologic information.